1992
DOI: 10.1093/oxfordjournals.jbchem.a123849
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in [3H]Ouabain Binding to Synaptic Plasma Membranes Isolated from Mouse Brains1

Abstract: Age-related changes in ouabain binding to synaptic plasma membranes isolated from cerebral cortices of C57BL/6 mice were investigated to examine whether the density of Na+, K(+)-ATPase decreases with advancing age. Specific binding of [3H]ouabain did not change until around 20 months of age, but a 22% decrease in binding was found in the late senescent stage (29 months). Scatchard analysis of the binding revealed that the maximum number of binding sites (Bmax) was lower in aged mice, while the binding affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Changes in molecular activity may occur, but at the present time this can only be implied. For example, brain synaptic membranes from 6-month-old mice show a 20% decrease in Na ‫ם‬ -K ‫ם‬ -ATPase activity, but sodium pump concentration does not decrease until 20 months of age, suggesting a decreased pump molecular activity with age (134).…”
Section: Older Agementioning
confidence: 99%
“…Changes in molecular activity may occur, but at the present time this can only be implied. For example, brain synaptic membranes from 6-month-old mice show a 20% decrease in Na ‫ם‬ -K ‫ם‬ -ATPase activity, but sodium pump concentration does not decrease until 20 months of age, suggesting a decreased pump molecular activity with age (134).…”
Section: Older Agementioning
confidence: 99%
“…Decrease in Na + -K + ATPase activity with an increase in age could result in neurotoxicity resulting in neuronal vulnerability to excitotoxic insults to the neuronal cells. Age related alterations of brain Na + -K + ATPase activity has been reported earlier [39] [40]. The activity of Na + -K + ATPase was measured using different concentrations of Aβ (25 -35), NKB and combined treatment of NKB and Aβ (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) in different age groups of control (without E2 treated) and E2 treated rat brain synaptosomes.…”
Section: Discussionmentioning
confidence: 87%
“…Scatchard analysis of the binding revealed that the maximum number of binding sites was lower in the aged, while the binding affinity for ouabain receptor remained unchanged. 21) The results indicate that the density of the Na + ,K + -ATPase decreases in the late senescent stage. However, the activity of the Na + ,K + -ATPase was found to start declining at a much earlier stage than that at which the decreased density of the enzyme was manifested.…”
Section: Synaptic Agingmentioning
confidence: 84%
“…This discrepancy may be explained by speculating that two different mechanisms responsible for the decrease of the enzyme activity are proceeding in aging, that is, the lipid microenvironment which regulates the enzyme activity starts to change at the early stage of senescence, followed by the decrease in the enzyme density in the later stage. 21) …”
Section: Synaptic Agingmentioning
confidence: 99%